Pengaruh Penggunaan Media Filtrasi Terhadap Kualitas Air Sumur Gali di Kota Sorong - Dwangga, Mierta; Yasin, Azalia Fajri; Tursina, Muhammad (Universitas Tanjungpura, 2023)
Sorong City is a city in Southwest Papua Province, with an area of 1,105 km2. The need for clean water is not directly proportional to the mapping of clean water services provided by the government so far it has not reached 30% of the total population in the Sorong City Region. The aims of the study were to analyze the existing water quality in Sorong City, to analyze the effect of the filter media on the planned filtration device on the water quality of the research sample, and to analyze the cost of the planned filtration device. The method used is a qualitative method that is carried out is the monitoring and interpretation of water quality data including physical and chemical quality. Observations of water from dug wells in the City of Sorong have the quality or nature of water that smells, has a salty taste, and is slightly brown in color. Of the 3 samples analyzed according to the existing location, only 2 samples were quality standards, the effect of the filtration media on water quality from 3 samples. Filtration equipment with filtration media 1 has an average per parameter of sample 1 of 25.78%, sample 2 of 36.59%, and sample 3 of 21.86%. The filtration device with 2 filtration media has an average sample 1 of 34.24%, sample 2 of 49.51%, and sample 3 of 25.44%. The filtration device with 3 filtration media has an average sample 1 of 22.32%, sample 2 of 30.6%, and sample 3 of 20.87%. and the cost of making a filtration device with filtration media 1 is IDR 300,000.00, filtration media 2 is IDR 295,000.00, filtration media 3 is IDR 290,000.00. The recommended filtration device is one that uses 2 filtration media.